Sex-Specific Associations of Genetically Predicted Circulating Lp(a) (Lipoprotein(a)) and Hepatic LPA Gene Expression Levels With Cardiovascular Outcomes: Mendelian Randomization and Observational Analyses. (19th July 2021) - Guertin, Jakie; Kaiser, Yannick; Manikpurage, Hasanga; Perrot, Nicolas; Bourgeois, Raphaëlle; Couture, Christian; Wareham, Nicholas J.; Bossé, Yohan; Pibarot, Philippe; Stroes, Erik S.G.; Mathieu, Patrick; Clavel, Marie-Annick; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Elevated Lp(a) (Lipoprotein(a)) levels are associated with coronary artery disease (CAD), ischemic stroke (IS), and calcific aortic valve stenosis (CAVS). Studies investigating the association between Lp(a) levels and these diseases in women have yielded inconsistent results. Methods: To investigate the association of Lp(a) with sex-specific cardiovascular outcomes, we determined the association between genetically predicted Lp(a) levels (using 27 single nucleotide polymorphisms at the LPA locus) and hepatic LPA expression (using 80 single nucleotide polymorphisms at the LPA locus associated with LPA mRNA expression in liver samples from the Genotype-Tissue Expression dataset) on CAD, IS, and CAVS using individual participant data from the UK Biobank: 408 403 participants of European ancestry (37 102, 4283, and 2574 with prevalent CAD, IS, and CAVS, respectively). The long-term association between Lp(a) levels and incident CAD, IS, and CAVS was also investigated in European Prospective Investigation into Cancer and Nutrition-Norfolk: 18 721 participants (3964, 846, and 424 with incident CAD, IS, and CAVS, respectively). Results: Genetically predicted plasma Lp(a) levels were positively and similarly associated with prevalent and incident CAD and CAVS in men and women. Genetically predicted plasma Lp(a) levels were associated with prevalent and incident IS when we studied men and women pooled together, and in men only. Genetically predicted LPA expression levels were associated with prevalent CAD and CAVS in men and women but not with IS. Conclusions: Genetically predicted blood Lp(a) and hepatic LPA gene expression as well as serum Lp(a) levels predict the risk of CAD and CAVS in men and in women. Whether RNA interference therapies aiming at lowering Lp(a) levels could be useful in reducing cardiovascular disease risk in both men and women with high Lp(a) levels needs to be determined in large-scale cardiovascular outcomes trials.